First ladies [compact disc] (American chronicles (National Public Radio (U.S.)), 2015)
While the role of the first lady has changed dramatically over the course of the nation's history, one thing remains constant: Americans have always been fascinated by the wives of the President. This collection features in-depth profiles of many of our beloved, inspiring, and occasionally enigmatic first ladies.